种污水处理用生物反应与吸附净水装置 (2018)
本发明涉及种污水处理用生物反应与吸附净水装置，包括沉淀池、曝气池、升温装置和吸附装置。所述沉淀池连接有曝气池，曝气池包括厌氧反应池、好氧池和空气压缩装置，曝气池后连接吸附装置。厌氧反应池内设有搅拌器，搅拌器的搅拌轴安装于厌氧反应池的顶部，其上安装有驱动叶轮；空气压缩装置包括空气压缩机，其出气口连接空气储罐；好氧池内设置有不少于1层的填料层，填料层附着生物膜，填料层的下方设置有曝气器；所述升温装置设于好氧池内，包括凸透镜、支架、保温层、进光筒和升温板，进光筒为圆柱形，进光筒内部为中空结构；所述吸附装置连接好氧池，内有不少于1层的吸附层，吸附层上下设有网状隔板，内有吸附剂，过滤后水通过管道排出。本发明有效处理了污水中的多种污染物，反应速度快，污水处理效率高。 The invention relates to a biological reaction and adsorption water purifying device used for waste water treatment. The biological reaction and adsorption water purifying device comprises a sedimentation basin, an aeration tank, a heating device, and an adsorption device; the sedimentation basin is connected with the aeration tank; the aeration tank comprises an anaerobic reaction tank, an aerobic tank, and an air compression device; the back part of the aeration tank is connected with the adsorption device; a stirrer is arranged in the anaerobic reaction tank; a stirring shaft of the stirrer is arranged on the top part of the anaerobic reaction tank, and the upper part of the stirr